Screen media dependency among pre-school children in Kuala Lumpur and its associated factors - Abdul Hadi, Azwanis; Abd Latip, Nurul Akmal; Samsudin, Suhaiza; Aidid, Edre Mohammad; Zakaria, Rozanizam (2022)
Earlier and prolonged screen media exposure to young children is associated with negative health concerns. Not much is known about screen media dependency among preschool children. This study aimed to measure its prevalence and associated factors among preschool children in Kuala Lumpur